PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KACANG HIJAU (Vigna radiata L.) - Puji Hastuti; Sumarmi Sumarmi; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
Research entitled The Effect of Planting Media Composition on Growth and Yield of Three Varieties of Mung Beans (Vigna radiata L.). The research was carried out on November 18, 2021 until January 17, 2022 at the Experimental Garden of the Faculty of Agriculture, Slamet Riyadi University, which is located on Jl. Jaya Wijaya No. 384, Mojosongo Village, Banjarsari District, Surakarta. The purpose of this study was to determine the best effect of the composition of the growing media on the growth and yield of three varieties of mung bean (Vigna radiata L.). The study used a Completely Randomized Resign (CRD) consisting of 2 treatment factors and 3 replications, the first factor was variety (V) with 3 levels, namely mung bean varieties Vima-1 (V1), Vima-4 (V2) and Vimil-2 (V3) and the second factor is the composition of the planting media with 4 levels, namely 2 Soil: 2 Cow manure (M1), 2 Soil: 2 Cow manure: 1 Sand (M2), 2 Soil: 1 Cow manure: 1 Husk charcoal ( M3), 1 Soil : 1 Cow manure : 1 Sand : 1 Husk charcoal (M4). The results showed that the best effect was found in the Vimil-2 variety with the composition of the planting media 1 Soil: 1 Cow manure: 1 Sand: 1 Husk charcoal (V3M4) on the number of pods per plant 31.67 pieces and the number of seeds per plant 487, 00 grains, Varieties Vima-4 in the treatment of planting media composition 2 Soil : 1 Cow manure : 1 Husk charcoal (V2M3) at a weight of 100 seeds the highest among the others 8.15 grams.